中國的北極戰略與挑戰 - 閻亢宗 (2014)
隨著北極冰雪加速融化，北極浮現的許多利益包括北極海上航線的開通以及潛在的自然資源等也開始受到矚目。這些利益也吸引中國的興趣，從其申請成為北極理事會永久觀察員即可看出。為了避免其他國家疑懼，中國目前採取多邊與雙邊外交等方式，強化它在北極的存在。雖然中國的北極策略已有一定成效，但仍面臨諸多挑戰，成為它進一步開拓北極的障礙。 With the onset of an accelerated sea-ice decline in the Arctic, discussions of the interests including opening of Arctic sea routes and of potential natural resources in the Arctic have erupted. To be sure, China displays a real interest in the Arctic, as attested by its applying for permanent observer in the Arctic Council. In order not to alarm other countries, China is currently adopting approaches of bilateral and multilateral diplomacy and other tactics as ways of enhancing its presence in the Arctic area. China has made some achievements in fulfilling its Arctic strategies. However, there are many challenges ahead and obstacles for China to further explore the Arctic.